Kendo as soft power and its role in Japan's cultural diplomacy with the Philippines - Bautista, Roehl Niño (Quezon City: Asian Center, University of the Philippines Diliman, 2022)
Kendo is a Japanese armed martial art that has its roots back to samurai swordsmanship. Although it has diffused globally both as a sport and martial art, there has been a dearth of scholarship written on the historic development of kendo, particularly in the Philippines. The increasing number of kendo clubs between 2010 and 2019, and the establishment of a national federation in 2016 indicate that kendo is currently growing in the country.

This research examines the recent popularity of kendo, and its role as Japan's soft power resource for promoting cultural relations with the Philippines. Using online surveys with Filipino kendoka belonging to the millennial and gen-z cohorts, semi-structured interviews with Filipino kendo practitioners, and profiling seven kendo clubs affiliated with the United Kendo Federation of the Philippines, the study finds that kendo's growth in the Philippines between 2010 to 2019 was primarily driven by Filipino practitioners, rather than by any program of the Japanese government or its affiliated organizations in the country. The Filipino kendoka's motivations for joining a kendo club, out of interest in Japanese culture and in the martial art itself, were also influenced by exposure to Japanese-related media and consumption of Japanese goods and cultural experiences. Filipino kendo clubs and kendoka nurture Japan's soft power in the Philippines, evident in their improved views and interests in Japan and Japanese culture.

Kendo in the Philippines, thus, contributes towards enhancing Philippines-Japan relations, functioning as a physical and virtual venue of interaction between states, federations, kendo clubs and kendoka, and transforming the Filipino kendoka into cultural ambassadors. Filipinos' interest in kendo cuts across not only between individuals and institutions, but also across time, space, and place.
Includes bibliographical references.
Thesis (Master of Arts in Asian Studies)
Keywords: Kendo; Hand-to-hand fighting, Oriental; Philippines -- Relations -- Japan; Japan -- Relations -- Philippines